La construcción del proyecto axiológico colectivo desde el paradigma postreligional - Corbí, Marià (Horizonte, 2015)
The techno-sciences accelerated growth, in continuous interaction, and the constant emergence of new products and services, in a global society, are leading in all countries to the biggest axiological crisis our species has ever suffered. All societies are in transition, from a preindustrial life to the industrial ones, and from industrial to societies of knowledge, innovation and continuous change. Knowledge Societies, inevitable legacy of our elders, are already been implanted in humanity, to stay and expand. The axiological collective projects (ACP), characteristic of preindustrial societies, with their religious paradigm, have been expelled from large social groups and have been called into question by the rest. Also ideologies of industrial societies are being shown in all parts unable to provide a ACP that address the problems that arise in the current transit. We know that the ACP can not come to us nor from heaven, nor from the nature of things. We have to build by ourselves, but our ancestors taught us no procedures to do that. Our urgent task is to create a knowledge about how to build an axiological epistemology. We have to create collective ACP from post-religional paradigm. At etake is our survival.